(untitled) (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2022)
Background: Most patients with Per Rectal Bleeding (PRB) warrant endoscopic examination of the lower GI tract. This study was done to determine the demographic profile and find out the etiology of bleeding per rectum under colonoscipic evaluation. Meterials and methods : In this study, we did a retrospective review of the clinical data of children between 0 and 18 years of age who presented with per rectalbleeding and underwent diagnostic and therapeutic colonoscopy in the Department of Pediatric Gastroenterology & Nutrition, Chattagram Maa-O-Shishu Hospital, Chattagram from July 2014 to July 2021.Patient demographics, clinical features and endoscopic and histopathological findings were recorded. Results: Overall, we included 111 patients with mean age 9.6±5.1 years. There were 69 (62.2%) male, 42(37.80%) female and with a male to female ratio of 1.64:1.0 The highest incidence was the age group of 11 to 18 years, 46 (41.40%). The most common colonoscopy finding were juvenile colorectal polyp 46 (41.44% ) which include rectal polyps 21 ( 18.9%), Sigmoid polyp 17 (15.3), recto sigmoid polyp 4 (3.6%), colonic polyp 4(3.6%), followed by internal hemorrhoids (20 cases, 18%) rectal ulcers (5 cases, 4.5%) colitis (4 cases, 3.60%) and findings suggestive of koach’s infection (2 cases, 1.8 %). All polyps were removed by colonoscopic polypectomy (47 cases 42.30%), 64 cases (57.65%) were given conservative treatment. Conclusion :We found that Juvenile colorectal polyps constitute the most common cause of per rectal bleeding in pediatric age group followed by hemorrhoids and colitis . Colonoscopy remains a useful and safe procedure in children for evaluation of lower GI bleeding and it’s good for both diagnostic and therapeutic procedure. Chatt Maa Shi Hosp Med Coll J; Vol.21 (1); January 2022; Page 66-69